Pemahaman Mahasiswa terhadap Sumber Rujukan Islam Digital dalam Pembelajaran Tafsir di Perguruan Tinggi - Johari Jamal; Rumni Hafiza; Lailatur Rahmi; Agil Saputra (Universitas Islam Negeri Imam Bonjol Padang, 2025)
The use of digital-based Islamic reference sources is increasing to support Tafsir learning. This article aims to analyze students' understanding of the use of digital Islamic reference sources, such as Syamila.net, Waqfeya.net, and Noor Book, as well as their implications in increasing digital literacy in Tafsir learning. This research used a quantitative descriptive approach and was conducted from October to December 2024. Respondents were students from UIN Batusangkar and UIN Imam Bonjol Padang who had completed the Tafsir Tarbawi and Tafsir courses. Data was collected through an online questionnaire using Google Form, which included questions regarding accessibility, frequency of use, and level of understanding of digital reference sources. The research results show that the majority of students have a good level of digital literacy, but there are still challenges in terms of source selectivity and utilization of available search features. In conclusion, although students' understanding of digital Islamic reference sources is sufficient, additional training is needed to optimize their digital literacy skills.